Perancangan Basis Data Menggunakan Normalisasi Tabel Pada Perusahaan Dagang Barokah Abadi - Sayyid Yakan Khomsi Pane; Nur Ghaniaviyanto Ramadhan; Faisal Dharma Adhinata (Research Group of Data Engineering, Faculty of Informatics, 2022)
Many human activities are related to information systems. Not only in developed countries, in Indonesia, information systems have been widely applied everywhere, such as in offices, supermarkets, airports, and even at home when users interact with the internet. Increased company operations in business activities can not be separated from information technology. The use of information technology is one of the effective steps in data processing, as well as business transactions using increasingly sophisticated computer equipment. A good database design plays a very important role in the performance and smooth running of an agency. So, in this research, a database design will be carried out with table normalization using MySQL at the Barokah Abadi trading company. This research also designs using entity relationship diagram (ERD).